2014
DOI: 10.3171/2014.7.jns132829
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant prophylaxis for brain tumor surgery: determining the current best available evidence

Abstract: Patients who undergo craniotomy for brain tumor resection are prone to experiencing seizures, which can have debilitating medical, neurological, and psychosocial effects. A controversial issue in neurosurgery is the common practice of administering perioperative anticonvulsant prophylaxis to these patients despite a paucity of supporting data in the literature. The foreseeable benefits of this strategy must be balanced against potential adverse effects and interactions with critical medications such as chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 72 publications
0
26
0
2
Order By: Relevance
“…Earlier studies have found that the highest incidence of seizures in the peri-operative period occurs within the first 7 days [20] . During this short timeframe, drug interactions and adverse events are less likely to occur as drug-induced hepatic enzyme induction generally requires 2 weeks of treatment [26] .Therefore, prescribing prophylactic AED for up to 1-2 weeks after surgery may be reasonable as long as patients are not maintained on AEDs in the long-term [20] .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Earlier studies have found that the highest incidence of seizures in the peri-operative period occurs within the first 7 days [20] . During this short timeframe, drug interactions and adverse events are less likely to occur as drug-induced hepatic enzyme induction generally requires 2 weeks of treatment [26] .Therefore, prescribing prophylactic AED for up to 1-2 weeks after surgery may be reasonable as long as patients are not maintained on AEDs in the long-term [20] .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, in a 2010 single center teaching hospital in Alberta, Lwu et al found the rate of seizure prophylaxis to be 27% [15] . Deviation from the guideline recommendations may be attributed to the perceived harms of seizures on the patients' psychosocial and physical well-being, especially during the immediate post-operative period where the risk of seizures is known to be higher [6,18,20] . Our center revealed a 28% prophylaxis rate overall, which is similar to the prophylaxis rate found by Lwu and colleagues in Alberta.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations